Making library websites accessible a practical guide for librarians - Francabandera, Laura, 1982- (Practical guides for librarians ;, 2018)
"This book will cover the basics of accessibility, foundational ethics and the current accessibility laws and regulations. It details the types of disabilities and challenges that patrons may face when accessing online information and can serve as an essential resource for testing any library website for accessibility"--